Associations of the atherogenic index of plasma with 28-day in-hospital mortality in patients with acute myocardial infarction: a retrospective cohort study from the eICU - Yan Wang; Hong-Fei Zhang (Lipids in Health and Disease)
Abstract Background Despite substantial advancements in treatment strategies, acute myocardial infarction (AMI) continues to exhibit high mortality. Recent research has identified the atherogenic index of plasma (AIP) as a significant measure of cardiovascular outcomes. However, the relationship between the AIP and 28-day mortality during hospitalization in AMI patients remains to be further clarified. Methods A retrospective analysis was conducted based on data sourced from the eICU Collaborative Research Database, encompassing records of 2,517 AMI patients treated in 208 critical care facilities across the U.S. from 2014 to 2015. AIP measurements were derived via log10 (triglyceride/high-density lipoprotein cholesterol) calculations. The primary endpoint was 28-day in-hospital mortality. The analysis utilized adjusted multivariable logistic models with restricted cubic splines for nonlinear associations. Subgroup analyses were performed to evaluate the relationships between AIP and mortality across various demographic and clinical subgroups. These subgroups included age, sex, body mass index (BMI), congestive heart failure, intubation status, mechanical ventilation, pneumonia, diabetes mellitus, antihyperlipidaemic agents, and AMI types. Results Among the 2,517 patients enrolled in the cohort (median age: 64.42 years), 138 (5.48%) died within 28 days. The analysis revealed a nonlinear association between the AIP and mortality, presenting a J-curve shape with a threshold of 0.60 (P for nonlinearity = 0.028). Each 0.1-unit elevation above 0.60 corresponded to a 22% increased mortality risk (adjusted OR = 1.22, 95% CI: 1.09–1.36; P = 0.0004). The highest AIP quartile had a 112% greater mortality risk than the lowest quartile (adjusted OR = 2.12, 95% CI: 1.15–3.88; P = 0.0154). Subgroup analyses revealed consistent patterns across the strata. Conclusion The relationship between the AIP and 28-day hospital mortality in AMI patients may be characterized by a J-shaped curve, where elevated AIP values are associated with increased mortality risk.